2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319336
|View full text |Cite
|
Sign up to set email alerts
|

In vivo NIRS monitoring in pig Spinal Cord tissues

Abstract: Little is known about the processes occurring after Spinal Cord damage. Whether permanent or recoverable, those processes have not been precisely characterized because their mechanism is complex and information on the functioning of this organ are partial. This study demonstrates the feasibility of Spinal Cord activity monitoring using Near Infra-Red Spectroscopy in a pig animal model. This animal has been chosen because of its comparable size and its similarities with humans. In the first step, optical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In particular, during periods of hypoxia and MAP alterations, changes in NIRS-derived SC oxygenated hemoglobin and tissue oxygenation percentage corresponded well with the changes in SC oxygen partial pressures measured by their intraparenchymal sensor. This study confirmed the results of the preliminary studies carried out on a pig model [ 62 , 63 ]. In 2018, D.R.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, during periods of hypoxia and MAP alterations, changes in NIRS-derived SC oxygenated hemoglobin and tissue oxygenation percentage corresponded well with the changes in SC oxygen partial pressures measured by their intraparenchymal sensor. This study confirmed the results of the preliminary studies carried out on a pig model [ 62 , 63 ]. In 2018, D.R.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, they concluded that NIRS monitoring could help surgeons prevent cord damage by providing real-time detection of the onset of ischemia and hypoxia, and hence allow intervention capable of restoring perfusion and oxygen delivery so as to prevent irreversible neuronal injury. Subsequently, several more recent studies have been conducted, notably on rabbits [ 55 ], sheep [ 56 , 57 , 58 ] or pig [ 59 , 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the notable inaccuracy prevents its utilization in advanced research applications as long as the calibration process is performed according to the empirical method (i.e., blood measurement on healthy, young volunteers) [1,21] on typical monitoring sites (finger, ear lobes, tongue). Thus, this 4% margin raises concerns when this technique is applied to fine monitoring or to investigate unusual locations such as the central nervous system [22][23][24][25] for example, mainly because it relies on device-specific characteristics, including the optoelectronic parts and the optical and geometrical properties of the tissues [26,27]. Moreover, the incorrect use of this empirical computational model is not device-specific, therefore inducing additional inaccuracies in the estimation of oxygen saturation.…”
Section: Introductionmentioning
confidence: 99%